Arterial stiffness in aortic stenosis - complex clinical and prognostic implications - Albu, Adriana; Para, Ioana; Bidian, Cristina (Biomedical papers, 2022)
Arterial stiffness and degenerative aortic stenosis (AoS) are frequently associated leading to a combined valvular and vascular load imposed on the left ventricle (LV). Vascular load consists of a pulsatile load represented by arterial stiffness and a steady load corresponding to vascular resistance. Increased vascular load in AoS has been associated with LV dysfunction and poor prognosis in pre-intervention state, as well as after aortic valve replacement (AVR), suggesting that the evaluation of arterial load in AoS may have clinical benefits. Nevertheless, studies that investigated arterial stiffness in AoS either before or after AVR used various methods of measurement and their results are conflicting. The aim of the present review was to summarize the main pathophysiological mechanisms which may explain the complex valvulo-arterial interplay in AoS and their consequences on LV structure and function on the patients' outcome. Future larger studies are needed to clarify the complex hemodynamic modifications produced by increased vascular load in AoS and its changes after AVR. Prospective evaluation is needed to confirm the prognostic value of arterial stiffness in patients with AoS. Simple, non-invasive, reliable methods which must be validated in AoS still remain to be established before implementing arterial stiffness measurement in patients with AoS in clinical practice.
Keywords: aortic stenosis; arterial stiffness; total left ventricle pressure load; ventriculo-arterial coupling